79‐4: Low Resolution Light Field Display for Improving the Perceived Openness of Confined Spaces. Issue 1 (29th May 2019) - Atkins, Robin; Whitehead, Lorne
Abstract : We introduce a novel light field display for enhancing the perception of open space in confined environments. We show that, counterintuitively, a perception of depth can be produced by a very low‐resolution light field display, which enables the use of a novel low‐cost optical design suitable for a wide range of applications. We present experimental verification that this design provides a convincing perception of depth.